DEVELOPMENT OF AN ENGLISH-SPEAKING MODULE FOR ISLAMIC BANKING STUDIES BASED ON THE PRESENT, PRACTICE, AND PRODUCTION (PPP) APPROACH - Yuda Septian Kurniawan; Agnes Yolanda; Ade Riska Nur Astari; Mahmood Rahimi (Linguists : Journal of Linguistics and Language Teaching, 2026)
This research aims to develop and test an English-speaking module for an Islamic Banking course using the Present, Practice, and Production (PPP) approach, an instructional sequence within Communicative Language Teaching. A preliminary study at three Islamic higher education institutions in Bengkulu Province found that lecturers and fifth-semester Islamic banking students lacked contextual, speaking-oriented English for Specific Purposes (ESP) teaching materials. The study employed a Research and Development design following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and used a mixed-methods approach; data from interviews, observations, and focus group discussions informed the need analysis and evaluation. In contrast, quantitative data from an expert-validation rubric and a student-response questionnaire established the module’s feasibility. The needs analysis revealed a dire need for transactional, banking-relevant speaking materials. The resulting module organizes banking and financial institution topics into PPP-based learning sequences across five units. Expert validation showed that the module was highly feasible (mean score = 87.75%). During the try-out, students responded positively across all five aspects—appeal, difficulty level, activity steps, technical vocabulary support, and practicality (mean = 87.8% positive). A supplementary classroom assessment further indicated that students’ mean speaking scores increased from 74 before to 88 after using the module. The findings suggest that a PPP-based ESP module can scaffold the technical vocabulary and transactional speaking skills required by Islamic banking graduates entering the workforce, and can serve as a model for ESP material development in other professional domains.